2017
DOI: 10.1007/s12602-017-9261-2
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Oral Probiotic Streptococcus salivarius K12 on Ear and Oral Cavity Health in Humans: Systematic Review

Abstract: Traditionally, probiotics are linked to the good health of the intestine and most clinical studies focus on that field. Evidence of oral probiotic use for ear and oral cavity disease prevention with impact on human health is limited. This work reviews existing studies and literature on Streptococcus salivarius K12 as an oral probiotic and effects of S. salivarius K12 on human ear and oral cavity human health. The studies were accessed via database searches: MEDLINE, PubMed, and Elsevier. The search included/fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0
6

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(56 citation statements)
references
References 30 publications
0
50
0
6
Order By: Relevance
“…Accordingly, we define them as biofilm CAGs. Streptococcus , a biofilm CAG, has promising results in treatment of halitosis, which often concurrent with digestive tract microbial disorders during the colorectal carcinogenesis 53 , 54 . In this study, the decrease of Streptococcus in the oral cavity of CRA group may contribute to microbiota dysbiosis-associated colorectal carcinogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, we define them as biofilm CAGs. Streptococcus , a biofilm CAG, has promising results in treatment of halitosis, which often concurrent with digestive tract microbial disorders during the colorectal carcinogenesis 53 , 54 . In this study, the decrease of Streptococcus in the oral cavity of CRA group may contribute to microbiota dysbiosis-associated colorectal carcinogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Streptococcus salivarius K12 appears to have excellent evidences as a kind of oral probiotic with more than a decade of tradition (Zupancic et al, ). It is reported that S. salivarius strains inhibit the biofilm formation of Streptococcus mutans and suppress potentially detrimental upper respiratory tract bacteria, such as Streptococcus pneumonia and Streptococcus pyogenes in vitro (James & Tagg, ; Ogawa et al, ; Tamura et al, ; Wescombe et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies revealed that S . salivarius K12 has the ability to interfere with the excessive growth of pathogens occupying the nasopharynx and oral cavity (Wescombe, Hale, Heng, & Tagg, ; Zupancic, Kriksic, Kovacevic, & Kovacevic, ). Accumulated evidence suggested that it is beneficial for otitis media (Pierro, Colombo, Giuliani, et al, ), halitosis (Burton, Chilcott, & Tagg, ; Masdea et al, ), and acute pharyngotonsillitis (Pierro, Colombo, Zanvit, & Rottoli, ) possibly due to its antimicrobial activity and immunomodulatory properties.…”
Section: Introductionmentioning
confidence: 99%
“…For example, S. salivarius strains can produce bacteriocin-like inhibitory substances with a broad spectrum of activity against cariogenic streptococci including S. mutans. S. oligofermentans is a bacterium that appears to be inversely correlated with the presence of S. mutans within dental plaque samples and was shown to produce hydrogen peroxide with lactic acid as the substrate, leading to the inhibition of S. mutans growth [112,113].…”
Section: Probiotics and Reducing Cariogenic Bacteriamentioning
confidence: 99%
“…e human oral cavity is in a state of coexistence with a microbial community [123]. Varieties of interactions between microbes normally maintain a balance in a healthy environment, while the overgrowth of conditional pathogens along with their increased virulence factors in the oral microenvironment disrupts this balance, leading to infectious diseases in the oral cavity, such as dental caries [113,[124][125][126]. e effect of microbial diversity and the interactions in microbial communities cannot be ignored.…”
Section: Consideration Of Microbial Interactions In Dental Plaquementioning
confidence: 99%